2010
DOI: 10.1074/jbc.m110.154575
|View full text |Cite
|
Sign up to set email alerts
|

A Synonymous Single Nucleotide Polymorphism in ΔF508 CFTR Alters the Secondary Structure of the mRNA and the Expression of the Mutant Protein

Abstract: Recent advances in our understanding of translational dynamics indicate that codon usage and mRNA secondary structure influence translation and protein folding. The most frequent cause of cystic fibrosis (CF) is the deletion of three nucleotides (CTT) from the cystic fibrosis transmembrane conductance regulator (CFTR) gene that includes the last cytosine (C) of isoleucine 507 (Ile507ATC) and the two thymidines (T) of phenylalanine 508 (Phe508TTT) codons. The consequences of the deletion are the loss of phenyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
172
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(184 citation statements)
references
References 64 publications
(56 reference statements)
9
172
0
1
Order By: Relevance
“…Decreased total receptor expression has been reported previously for some missense GPCR mutations including the MC4R (Fan & Tao 2009, Wang & Tao 2011, Yang & Tao 2012, Zhang et al 2012, even for some synonymous mutations (Duan et al 2003, Bartoszewski et al 2010. We therefore further studied whether the decreased total receptor expression was due to accelerated protein degradation (Yang et al 2011).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Decreased total receptor expression has been reported previously for some missense GPCR mutations including the MC4R (Fan & Tao 2009, Wang & Tao 2011, Yang & Tao 2012, Zhang et al 2012, even for some synonymous mutations (Duan et al 2003, Bartoszewski et al 2010. We therefore further studied whether the decreased total receptor expression was due to accelerated protein degradation (Yang et al 2011).…”
Section: Discussionmentioning
confidence: 86%
“…These results suggested that increased degradation by the proteasome or lysosome was not responsible for the diminished expression of these mutants. Decreased protein synthesis due to altered secondary structure of mRNA (Duan et al 2003, Bartoszewski et al 2010) of those MC4R mutants might be responsible for the decreased receptor expression, although posttranscriptional mechanisms might also be involved. Further studies are needed to address the detailed causes of the observed decreased total MC4R expression.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the process by which proteins fold during their biosynthesis is one of the most fundamental problems in molecular biology, as it is crucial to enable their biological function 3,40 , and its failure can result in their misfolding [40][41][42] , malfunction 7 and aggregation 3,4,43 , events that are associated with a wide range of severe health conditions including neurodegenerative disease 44 . A key challenge in this context is to interpret and predict the influence of individual codon translation rates on cotranslational protein folding and misfolding.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that the synonymous codon change of I507 in the F508 allele can cause mRNA misfolding, leading to reduced rate of translation and/or impaired cotranslational folding of F508 CFTR (Bartoszewski et al, 2010). Therefore, codon-dependent mRNA folding represents a new mechanism by which F508 CFTR expression can be regulated.…”
Section: Elevating F508 Cftr Expressionmentioning
confidence: 99%